Development and Validation of a LASSO Prediction Model for Better Identification of Ischemic Stroke: A Case-Control Study in China - Meng, Zirui; Wang, Minjin; Guo, Shuo; Zhou, Yanbing; Zheng, Mingxue; Liu, Miaonan; Chen, Yongyu; Yang, Zhumiao; Zhao, Bi; Ying, Binwu (Frontiers in Aging Neuroscience, 2021)
Background Timely diagnosis of ischemic stroke in the acute phase is extremely vital to achieve proper treatment and good prognosis. In this study, we develop a novel prediction model based on the easily obtained information at initial inspection to assist the early identification of ischemic stroke. Methods A total of 627 patients with ischemic stroke and other intracranial hemorrhagic diseases from March 2017 to June 2018 were retrospectively enrolled in the derivation cohort. Based on their demographic information and initial laboratory examination results, the prediction model was constructed. The least absolute shrinkage and selection operator algorithm was used to select the important variables to form a laboratory panel. Combined with the demographic variables, multivariate logistic regression was performed for modeling, and the model was encapsulated within a visual and operable smartphone application. The performance of the model was evaluated on an independent validation cohort, formed by 304 prospectively enrolled patients from June 2018 to May 2019, by means of the area under the curve (AUC) and calibration. Results The prediction model showed good discrimination (AUC = 0.916, cutoff = 0.577), calibration and clinical availability. The performance was reconfirmed in the more complex emergency department. It was encapsulated as the Stroke Diagnosis Aid APP for smartphones. The user can obtain the identification result by entering the values of the variables in the graphical user interface of the application. Conclusions The prediction model based on laboratory and demographic variables could serve as a favorable supplementary tool to facilitate complex, time-critical acute stroke identification.